Dividend policy of Nepalese non-financial enterprises - Dhital, Yubaraj (Medha: A Multidisciplinary Journal, 2023)
This study examines the effect of Market price per share, earnings per share, net profit margin, return on assets and degree of leverage on dividend per share and dividend payment ratio of Nepalese non-financial enterprises. The samples used in this research are manufacture companies, hydropowers and hotels & others listed in Nepal Stock Exchange (NEPSE). Earnings per share, net profit margin, return on assets and degree of leverage are independent variables and market price per share, dividend per share and dividend payout ratio used as dependent variables. The study examines a total of 17 Nepalese non-financial enterprises with 124 observations during the period from 2066/67 to 2075/76 B.S. The descriptive and correlation models are estimated to test the significance and importance of Market price per share, earnings per share, net profit margin, return on assets, degree of leverage on dividend policy of Nepalese non-financial firms. The result showed that market price per share, earning per share, net profit margin, return on assets, have significant positive effect on dividend policy. Similarly, debt equity ratio has negative impact on dividend policy. Likewise, earning per share has negative impact on dividend payout ratio. The results of this study are expected to be implemented by the financial managers in improving market price per share and signaling effect of dividend policy.